The decoration on the cult chapel walls of the Old Kingdom tombs at Giza: a new approach to their interaction - Roeten, Leo (Culture and history of the ancient Near East, 2014)
In The Decoration on the Cult Chapel Walls of the Old Kingdom Tombs at Giza Leo Roeten demonstrates that the 5th dynasty was a period of drastic changes in the mode of food supply for the deceased, the type of decoration on the walls, and the secondary cultic functions